A systematic analysis of worldwide population-based data on the global burden of chronic kidney disease in 2010 - Mills, Katherine T.; Xu, Yu; Zhang, Weidong; Bundy, Joshua D.; Chen, Chung-Shiuan; Kelly, Tanika N.; Chen, Jing; He, Jiang (Kidney international, 2015)
Chronic kidney disease (CKD) is a major risk factor for endstage renal disease, cardiovascular disease, and premature death. Here we estimated the global prevalence and absolute burden of CKD in 2010 by pooling data from population- based studies. We searched MEDLINE (January 1990 to December 2014), International Society of Nephrology Global Outreach Program-funded projects, and bibliographies of retrieved articles and selected 33 studies reporting gender- and age-specific prevalence of CKD in representative population samples. The age-standardized global prevalence of CKD stages 1–5 in adults aged 20 and older was 10.4% in men (95% confidence interval 9.3–11.9%) and 11.8% in women (11.2–12.6%). This consisted of 8.6% in men (7.3–9.8%) and 9.6% in women (7.7–11.1%) in high-income countries, and 10.6% in men (9.4–13.1%) and 12.5% in women (11.8–14.0%) in low- and middle-income countries. The total number of adults with CKD was 225.7 million (205.7–257.4 million) men and 271.8 million (258.0–293.7 million) women. This consisted of 48.3 million (42.3–53.3 million) men and 61.7 million (50.4–69.9 million) women in high-income countries, and 177.4 million (159.2–215.9 million) men and 210.1 million (200.8–231.7 million) women in low- and middle-income countries. Thus, CKD is an important global-health challenge, especially in low- and middle-income countries. National and international efforts for prevention, detection, and treatment of CKD are needed to reduce its morbidity and mortality worldwide.